2019
DOI: 10.1055/s-0039-1698469
|View full text |Cite
|
Sign up to set email alerts
|

Choosing between Muscle and Fasciocutaneous Free Flap Reconstruction in the Treatment of Lower Extremity Osteomyelitis: Available Evidence for a Function-Specific Approach

Abstract: Background Limb salvage in the setting of extremity osteomyelitis, though previously dependent on amputation, has been markedly improved through the application of free tissue flaps. Concern exists as to the utility of the fasciocutaneous flap to combat infection verses the traditional muscle flap. Prior studies have shown success with fasciocutaneous flaps in these patients, but given the small series, the choice remains controversial. The goal of this article was to determine if there is statistical evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
2
28
1
Order By: Relevance
“…Vancomycin has an incomparable effect in the treatment of Gram-positive cocci. In recent years, it has been used more and more in the treatment of bone infections [18][19][20]. It basically treats all pathogens that may cause chronic osteomyelitis.…”
Section: Related Workmentioning
confidence: 99%
“…Vancomycin has an incomparable effect in the treatment of Gram-positive cocci. In recent years, it has been used more and more in the treatment of bone infections [18][19][20]. It basically treats all pathogens that may cause chronic osteomyelitis.…”
Section: Related Workmentioning
confidence: 99%
“…Fasciocutaneous flaps, with its vast application opportunities have evolved into workhorse flaps for soft tissue reconstruction after trauma, showed lower recurrence rates after osteomyelitis and lower complication rates compared with muscle flaps for lower extremity reconstruction. 20,21 The study underlines the relevance of fasciocutaneous flap and is the reason why it is indicated as the workhorse flap for extremity reconstruction in our department. Approximately 54% of all free flaps of cohort A and 33% of cohort B were ALT flaps.…”
Section: Discussionmentioning
confidence: 95%
“…The important characteristics of osteomyelitis are recurrent infection and resistance to treatment. The recurrence rate of osteomyelitis is an important index to evaluate the effectiveness of surgery, and it is 4.3% ~ 28% as reported in the literature 27 , 28 . In this series, all defects were associated with various degrees of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%